Systems theory for social work and the helping professions - Schirmer, Werner, ....-; Michailakis, Dimitris, ....- (London : Routledge, 2019)
Social systems occur in many contexts of social work. This book provides an easy-to-read introduction to systems thinking for social workers who will encounter social problems in their professional practice or academic research. It offers new insights and fresh perspectives on this familiar topic and invites creative, critical, and empathetic thinking with a systems perspective. Through introducing systems theory as a problem-oriented approach for dealing with complex interpersonal relations and social systems, this book provides a framework for studying social relations. The authors present a strand of systems theory (inspired by sociologist Niklas Luhmann) that offers innovative, surprising, and practically relevant understandings of everyday social life, inclusion/exclusion, social problems, interventions, and society in general. Systems Theory for Social Work and the Helping Professions should be considered essential reading for all social work students taking modules on sociology and social policy as well as students of nursing, medicine, counselling, and occupational health and therapy.